Ambient Synthesis of One‐/Two‐Dimensional CuAgSe Ternary Nanotubes as Counter Electrodes of Quantum‐Dot‐Sensitized Solar Cells. Issue 4 (12th February 2016) - Chen, Xin Qi; Bai, Yang; Li, Zhen; Wang, Lian Zhou; Dou, Shi Xue
Abstract: Invited for this month's cover is the group of Prof. Zhen Li. The highlighted study results from a collaboration between the University of Wollongong, University of Queensland, Soochow University, and Central China Normal University. Ternary copper silver selenide nanotubes were prepared and explored as high‐performance counter electrodes in quantum‐dot‐sensitized solar cells. Read the full text of the article at 10.1002/cplu.201500466 . Abstract : "… In future we plan to investigate the nanomedical applications of binary and ternary metal chalcogenide nanostructures. …" Read more about the story behind the cover in the Cover Profile and about the research itself (DOI: 10.1002/cplu.201500466 ).